Dietary arginine silicate inositol complex during the late laying period of quail at different environmental temperatures - Onderci, M; Şahin, Nurhan; Şahin, Kazım; Balci, TA; Gursu, MF; Juturu, V; Küçük, Ömer (Taylor & Francis Ltd, 2006)
1. Arginine silicate inositol complex (ASI dagger; arginine 49.5%, silicon 8.2%, inositol 25%) is a novel material which is a bioavailable source of silicon and arginine. ASI offers potential benefits for vascular and bone health. 2. Poor eggshell quality has been a major economic concern to commercial egg producers. Poor egg quality, skeletal abnormalities and architectural deterioration of bone tissue are common problems under hot conditions and in older birds. 3. The effects of ASI supplementation on egg production, egg quality, levels of osteocalcin (OC) and bone mineral content were investigated in heat-stressed Japanese quail during the later part of the laying period. 4. The birds were randomly assigned to six treatment groups consisting of six replicates of five birds each in a 2 x 3 factorial arrangement of treatments (temperatures, ASI levels). The birds were kept in wire cages in a temperature-controlled room at either 22 degrees C (TN) or 34 degrees C ( HS) for 8 h/d and fed either a basal ( control) diet or the basal diet supplemented with either 500 or 1000 g of ASI/kg. 5. Heat exposure reduced egg production, egg quality and bone mineralisation when the basal diet was fed. ASI supplementation had no effect on feed intake or egg production under TN or HS conditions. However, ASI supplementation increased egg weight, shell thickness, shell weight and Haugh unit in both TN and HS groups during the late laying period. Bone mineral density (BMD) was significantly improved by ASI supplementation in both TN and HS groups. Serum osteocalcin (OC) concentrations and alkaline phosphatase ( ALP) activity increased linearly with dietary ASI supplementation during the late laying period. The amount of calcium and phosphorus in the excreta decreased, while ash, mineral content, calcium and phosphorus concentrations in tibia increased in ASI-supplemented quail in both TN and HS groups during the late laying period. 6. ASI supplementation significantly improved egg quality and bone mineralisation in quail during the late laying period and did not affect feed consumption or egg production.
Keywords: Ambient-Temperature; Bone Loss; Amino-Acids; Performance; Supplementation; Heat; Balance; Stress; Lysine; Age